Functions, methods and concepts in evaluation research - Stockmann, Reinhard; Meyer, Wolfgang; SpringerLink (Online service) (London : Palgrave Macmillan UK, 2013)
By explaining the role of evaluation in modern societies and its historical development in the USA and Europe this book highlights the scientific roots of Evaluation and offers an overview of its fundamental theories and concepts. The process of collecting, analyzing and interpreting is explored giving an insight into the course of an evaluation.
Keywords: Science; Science, general